Immovable object, irresistible force: Reith, Churchill and BBC ‘impartiality’ - Trevor Harris (Cahiers du MIMMOC)
Both Churchill and Reith were convinced of the importance of their personal mission in public life. While the BBC was still a private company the two clashed during the General Strike; several other confrontations would follow. The mutual animosities generated lasted into the 1940s. Churchill’s desire to bend broadcasting to his personal political ends was countered by Reith’s staunch defence of public service broadcasting which should be as independent as possible from, and should not represent, government or specific political interests. Reith, profoundly conservative, nonetheless resisted Churchill’s own aggressive conservatism. Reith disliked and distrusted Churchill, believing that the only reliable way to protect the BBC’s fragile independence was to accept limitations to impartiality. Only in that way, Reith felt, could the BBC continue to serve the public in the most efficient, useful way, providing the greatest possible audience with the greatest possible access to the best possible programmes.